y = 3Cosx + 2Sin²x - 1
Найдём производную :
y' = (Cosx)' + 2(Sin²x)' - 1' = - 3Sinx + 4SinxCosx
Приравняем производную к нулю :
- 3Sinx + 4SinxCosx = 0
Sinx(- 3 + 4Cosx) = 0
Sinx = 0
- 3 + 4Cosx = 0
Cosx = 0,75
Если Sinx = 0 , то Cosx = ± 1
1) Sinx = 0 ⇒ Cosx = - 1 ⇒
y = 3 * (- 1) + 2 * 0 - 1 = - 4 - наименьшее
2) Sinx = 0 ⇒ Cosx = 1 ⇒
y = 3 * 1 + 2 * 0 - 1 = 2
3) Cosx = 0,75 ⇒ Sin²x = 1 - Cos²x = 1 - 0,75² = 1 - 0,5625 = 0,4375
y = 3 * 0,75 + 2 * 0,4375 - 1 = 2,25 + 0,875 - 1 = 2,125 - наибольшее
ответ : наименьшее - 4 , наибольшее 2,125
1) x=6, y=-29
2)x=-2, y=3
Объяснение:
1)y=1-5x
11x+2(1-5x)=8
11x+2-10x=8
x+2=8
x=6
y= 1-5*6= 1-30=-29
2) x= 5y-21/3
7(5y-21)/3+10y=16
умнажаем все на 3, чтобы избавиться от дроба
7(5y-21)+30y=48
35y-147+30y=48
65y=195
y=3
x= (5*3-21)3= 15-21/3=-2